Synthesis and Characterization of Nanomaterials from Porang (Amorphophallus muelleri) and Its Application for Bioplastic: Preliminary - Esa Ghanim Fadhallah; Lathifa Indraningtyas; Teguh Setiawan; Iqbal Firdaus; Andri Pratama (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
The increase in plastic waste caused by population growth and human activities is capable of leading to negative consequences for the environment. The substantial accumulation contributes to environmental pollution since its resilience against microbial degradation poses a significant challenge. Furthermore, the utilization of bioplastics as a biodegradable substitute presents a viable strategy for diminishing reliance on synthetic plastics. Starch emerges as a prevalent primary component in the fabrication of bioplastics, owing to its array of merits including renewability, cost-effectiveness, non-toxicity, and facile degradability. The application of nanomaterials to bioplastics is believed to accelerate the degradation of bioplastics. Therefore, this study aimed to identify the characteristics of nanomaterial from porang (Amorphophallus muelleri) and bioplastic. The method included the extraction of porang nanomaterial through a specified water-to-porang ratio (2.5:1) followed by sonication (50 W, 75 minutes). The formulation of bioplastics involved the amalgamation of corn starch, porang nanomaterial, and glycerol. In addition, the chemical properties of porang nanomaterials included 41.41% starch content, 13.49% amylose, 7.87% ash, and 2.52% calcium oxalate. The particle size of porang nanomaterials was distributed from 603.7-952.1 nm with an average 722.6 nm crystalline structure containing calcium oxalate. The bioplastic had the form of a thin brown layer with a thickness value ranging from 0.23-0.39 mm. This research was expected to provide new information related to the essential characteristics of nanomaterials from porang and its potential application in solving environmental issues caused by synthetic plastics.